Aktor Collaboration in Providing Housing For Low-Income People (MBR) - Widyastuti, Yeni (Prodi Administrasi Publik FISIP UNPAS, 2024)
This journal discusses Action Collaboration in the vision of housing for Low-Income Communities (MBR). With limited access to affordable housing, Low-Income Communities often have difficulty finding suitable housing. Therefore, a policy network strategy is needed to overcome these problems and improve the welfare of Low-Income Communities (MBR). Efforts are needed to realize livable, healthy, and safe housing, which is supported by infrastructure, facilities, and public works that support quality improvement and educate development. Meanwhile, the local government issued a special housing policy related to the vision of housing for Low-Income Communities (MBR). It is necessary to have a common view of settlement by the Low-Income Community (MBR), based on the preferences of the Low-Income Community (MBR) settlement and adjustments to the settlement policy applied, especially with regard to the safety and comfort of the people living in the settlement. The development of low-income housing is not in accordance with the scale of the policy network that includes the role of the community itself. The role of the community itself is not directly involved, their aspirations and complaints are currently only channeled through Non-Governmental Organizations (NGOs), so they tend to be less active. Political networks lack functioning mechanisms, and the lack of regular meetings between actors puts little emphasis on cooperation, making it difficult for actions to optimally utilize existing information channels.